IR-induced and tunneling reactions in cryogenic matrices: the (incomplete) story of a successful endeavor - Fausto, Rui (2022)
In this article, IR-induced and tunneling-driven reactions observed in cryogenic matrices are described in a historical perspective, the entangling of the two types of processes being highlighted. The story of this still ongoing fascinating scientific endeavor is presented here following closely our own involvement in the field for more than 30 years, and thus focuses mostly on our work. It is, because of this reason, also an incomplete story. Nevertheless, it considers a large range of examples, from very selective IR-induced conformational isomerizations to IR-induced bond-breaking/bond-forming reactions and successful observations of rare heavy atom tunneling processes. As a whole, this article provides a rather general overview of the major progress achieved in the field.